Economic transition in the GDR and CSSR - Bofinger, Richard; Lipka, David; Žamberský, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
Former socialist countries underwent an important economic transition starting in 1989. The German Democratic Republic (GDR) in this regard is a somewhat special case. The reunification with Western Germany reprieved the former GDR from many problems Czechoslovakia (CSSR) had to face and consequently in the first place led to a smoother transition to democracy and market economy. Evidence suggests, however, that the original advantage of immediate adoption of good institution was not a decisive element in the success of economic transition. This thesis aims at comparing the case of economic transition in the GDR and CSSR/Czech Republic after 1989. It will assess the relative importance of institutions, policies, transfers, and private investments for the success of reforms in the two countries.
Vedoucí práce: David Lipka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses